Facilitating online learning environment in math classes: Teachers' views and suggestions - Esra Karaca; Didem Akyuz (Journal of Pedagogical Research, 2024)
This study aims to reveal the views and suggestions of in-service mathematics teachers about supporting online learning. Many times, studies indicate the teachers' views related to the advantages and disadvantages of online learning. However, limited studies investigate teachers' views for improving the online learning environment. Thus, this study reveals teachers' recommendations for supporting e-learning. To achieve this, a case study was conducted to describe teachers' views. Data were collected from four middle and high school mathematics teachers through interviews, reflections, and lesson plans for online mathematics education courses. Teachers' views and suggestions related to supporting online learning were coded under five categories: norms, selection of manipulatives, building a community of learners, participation in group work, and assessment in the online learning environment.